The Pengaruh Interaksi Orang Tua dan Anak Terhadap Perilaku Sosial Remaja Kota Pekanbaru - Hidayat, Novrely Shaqinah (Fakultas Studi Islam Universitas Muhammadiyah Riau, 2025)
This research aims to determine the influence of parent-child interaction on the social behavior of adolescents in Pekanbaru City. The study employs a quantitative approach with data collection techniques through questionnaires distributed to adolescents in Pekanbaru City. The analysis results indicate that parent-child interaction has a significant effect on adolescent social behavior, with a significance value of 0.001 (p < 0.05). This interaction contributes 16.3% to social behavior, while 83.7% is influenced by other factors such as individual characteristics, cognitive processes, environment, and culture. It can be concluded that positive interaction between parents and children plays a role in shaping adolescent social behavior. Therefore, it is recommended that parents become more actively involved in interactions with their children to support healthy social development. Keywords: Parent-Child Interaction, Social Behavior, Adolescents